2009
DOI: 10.1111/j.1460-2695.2008.01306.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of constraint effects in fracture mechanism transition for cracked structures under mixed mode loading

Abstract: A B S T R A C TThe objective of the study is to evaluate the effects of plastic constraint on transition between tensile-type and shear-type fracture . The T-stress is employed as the quantifying parameter for constraint and is incorporated into the existing theoretical criteria for modelling this transition. It is found that different constraint levels can dramatically alter the transition point. To verify this finding, two sets of mixed mode tests with different constraint levels are carried out. Alongside t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…To examine whether or not the stress triaxiality factor T f is a general measure of constraint for ductile material A508, the T f at a characteristic distance of r c = 0.5 mm ahead of the crack tips at J = J IC was calculated and investigated 9,20 . The T f was defined as: where σ m is the hydrostatic stress and is the von Mises equivalent stress.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…To examine whether or not the stress triaxiality factor T f is a general measure of constraint for ductile material A508, the T f at a characteristic distance of r c = 0.5 mm ahead of the crack tips at J = J IC was calculated and investigated 9,20 . The T f was defined as: where σ m is the hydrostatic stress and is the von Mises equivalent stress.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…Later it was found that the description of out‐of‐plane constraint should include an additional parameter such as a body size in the z ‐direction or the specimen thickness. The authors of Refs 1–8 presented description of the thickness effect on crack‐tip constraint on the basis of numerical results. In particular, authors 9,10 stayed that three‐dimensional (3D) constraint effect along the crack front in a thin plate and in thick SENB specimens can be well represented by the J − A 2 solution accounting for the higher‐order terms under both small‐scale yielding and large‐scale yielding conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Ayatollahi and his co‐workers modified the SED criterion, also considering the effects of T ‐stress as well as SIFs. The modified fracture criteria mentioned previously can provide better predictions for mixed mode brittle fracture compared with the conventional fracture criteria, which ignore the influence of T ‐stress . The T ‐stress as well as SIFs have been recognized as two significant parameters in brittle or quasi‐brittle fracture …”
Section: Introductionmentioning
confidence: 99%
“…The modified fracture criteria mentioned previously can provide better predictions for mixed mode brittle fracture compared with the conventional fracture criteria, which ignore the influence of T-stress. [7][8][9][10][12][13][14][15][16][17] The T-stress as well as SIFs have been recognized as two significant parameters in brittle or quasi-brittle fracture. 18,19 In addition to the energy and stress-based criteria, some strain-based criteria have been also put forward during the past few decades.…”
Section: Introductionmentioning
confidence: 99%